Dietary vitamin K is remodeled by gut microbiota and influences community composition. (1st January 2021) - Ellis, Jessie L.; Karl, J. Philip; Oliverio, Angela M.; Fu, Xueyan; Soares, Jason W.; Wolfe, Benjamin E.; Hernandez, Christopher J.; Mason, Joel B.; Booth, Sarah L.
ABSTRACT: Vitamins have well-established roles in bacterial metabolism. Menaquinones (MKn, n = prenyl units in sidechain) are bacterially produced forms of vitamin K produced by the gut microbiota and consumed in the diet. Little is known about the influence of dietary vitamin K quinones on gut microbial composition and MKn production. Here, male and female C57BL6 mice were fed a vitamin K deficient diet or vitamin K sufficient diets containing phylloquinone (PK, plant-based vitamin K form), MK4, and/or MK9. DNA was extracted from cecal contents and 16S sequencing conducted to assess microbial composition. Cecal microbial community composition was significantly different in vitamin K deficient female mice compared to females on vitamin K sufficient diets (all p < .007). Parallel trends were seen in male mice, but were not statistically significant (all p > .05 but <0.1). Next, stable isotope-labeled vitamin K quinones were supplemented to male and female C57BL6 mice ( 2 H7 PK, 13 C11 MK4, 2 H7 MK7, 2 H7 MK9) and to an in vitro fermentation model inoculated with human stool ( 2 H7 PK, 2 H7 MK4, 2 H7 MK9, or vitamin K precursor 2 H8 -menadione). Vitamin K quinones in feces and culture aliquots were measured using LC-MS. In vivo, supplemented vitamin K quinones were remodeled to other MKn ( 2 H7 - or 13 C6 -labeled MK4, MK10, MK11, and MK12), but in vitro only the precursor 2 H8 -menadione was remodeled to 2 H7 MK4, 2 H7 MK9, 2 H7 MK10, and 2 H7 MK11. These results suggest that dietary vitamin K deficiency alters the gut microbial community composition. Further studies are needed to determine if menadione generated by host metabolism may serve as an intermediate in dietary vitamin K remodeling in vivo .